Non-invasive fibrosis tools lack clinical utility for identifying advanced fibrosis in Fontan-associated liver disease: a retrospective cohort study - Stephen Stewart; Robert Hughes; Kevin Walsh; Paul Armstrong; Aoife Moriarty; Niamh Mehigan; Rhona Savage; Jennifer Russell (BMJ Open Gastroenterology)
Objective Fontan-associated liver disease (FALD) results from haemodynamic changes following the Fontan procedure for congenital heart disease and is associated with poorer outcomes. The prevalence of Fontan is rising due to improved survival; however, little is known about predictors of advanced liver fibrosis in adult patients. This study aimed to determine the accuracy of non-invasive fibrosis assessment tools (NIT) in predicting histologically confirmed advanced liver fibrosis in an adult Fontan cohort attending Mater Misericordiae University Hospital.Methods Patient demographics, congenital cardiac variables and fibrosis biomarkers were recorded including liver stiffness measurement (LSM) via transient elastography, Fibrosis-4 (FIB-4) and Aspartate aminotransferase-to-Platelet Ratio Index (APRI) scores. Biopsies, taken between 2017 and 2024, were staged using the congestive hepatic fibrosis score. Analysis was performed using SPSS.Results 71 patients (58% male) were included. The median age was 25 years. 62% had histological advanced fibrosis. There were no significant bleeding events post biopsy. Overall, advanced fibrosis was associated with a closed Fontan fenestration (p=0.022) and higher LSM, although with a weak correlation (p=0.04, r=0.25, area under the curve (AUC) 0.65), but not with APRI or FIB-4. There was no difference in rates of advanced fibrosis between sex (p=0.84). In females, higher APRI was associated with advanced fibrosis (p=0.045, r=0.41, AUC 0.73).Conclusions The majority of Fontan patients have advanced liver fibrosis in their third decade. A patent Fontan fenestration appears to reduce the risk of advanced fibrosis. Despite an association with higher LSM, there was no cut-off which could negate the need for biopsy in a significant population. Our data suggest that the discriminatory ability of NIT may vary according to sex. Liver biopsy is safe and remains the only method of reliably diagnosing advanced fibrosis in FALD.